An Evolutionary Theory of Human Motivation. (Genetic, Social & General Psychology Monographs, 2005)
The authors review psychology's historical, competing perspectives on human motivation and propose a new comprehensive theory. The new theory is based on evolutionary principles as proposed by C. Darwin (1859) and modified by W. D. Hamilton (1964, 1996) R. , Trivers (1971,1972), and R. Dawkins (1989). The theory unifies biological, behavioral, and cognitive approaches to motivation. The theory is neuropsychological and addresses conscious and nonconscious processes that underlie motivation, emotion, and self-control. The theory predicts a hierarchical structure of motives that are measurable as individual differences in human behavior. These motives are related to social problem domains (D. B. Bugental, 2000; D. T. Kenrick, N. P. Li, & J. Burner, 2003), and each is hypothesized to solve a particular problem of human inclusive fitness. Reprinted by permission of the publisher.